IMPLEMENTASI CLOUD COMPUTING TECHNOLOGY DAN DAMPAKNYA TERHADAP KELANGSUNGAN BISNIS PERUSAHAAN DENGAN MENGGUNAKAN METODE AGILE DAN STUDI LITERATUR - Riana, Eri (JURIKOM (Jurnal Riset Komputer), 2020)
Cloud Computing technology is a new paradigm in the delivery of computing services, Cloud Computing has many advantages compared to conventional systems usually. The development of business at this time began to compete globally to be able to satisfy customers, so companies need access to information that is fast and accurate. In order to access information quickly, companies need to build Information and Communication Technology infrastructure that requires large capital, on the other hand cloud computing is present as an alternative solution. Services provided by cloud computing include hardware, infrastructure, platforms and applications. Cloud computing is very useful, because it can reduce computing costs, increase reliability and provide considerable opportunities for the industrial world. One company that provides cloud computing services is Google. The features of cloud computing are believed to be far more efficient and satisfying. The problem that arises is how companies implement Cloud Computing using Google Cloud and how to carry out the process of deployment and provisioning of Google Cloud SQL Database. The purpose of this research is to provide a study of the benefits of implementing Google Cloud for companies to improve business competitiveness so tightly. This research uses Agile method and literature study, which begins with planning, implementation, testing, documentation, deployment, maintenance, problem identification and analysis and discussion related to Google Cloud, where the results of this research are that Google Cloud can create a model business is more flexible, and faster. The purpose of writing this journal is to provide an overview of the understanding of cloud computing and its development as well as the advantages and disadvantages of companies that use Cloud Computing technology. Based on these searches it is known that Cloud Computing as a technology that utilizes internet services uses a virtual central server for the purpose of maintaining data and applications. The existence of Cloud Computing itself has caused changes in the workings of information technology systems in a company. Security and data storage systems are important for companies. Cloud Computing technology has provided huge benefits for most companies. To carry out the process, the device needs to be prepared include hardware such as HPE DL 20 Gen 10 E-2136-4 SFF Server Computer, 2x1 TB SATA 7.2K 3.5 "Hard Drive, 256GB RAM, minimum bandwidth of 5 Mbps and software requirements including Windows Server 2012 R2 Enterprise, VMM, Google Cloud Platform Enterprise, SQL Server 2012